Quantitative analysis of the relationship between nucleotide sequence and functional activity. - Stormo, G D (1986)
Matrices can be used to evaluate sequences for functional activity. Multiple regression can solve for the matrix that gives the best fit between sequence evaluations and quantitative activities. This analysis shows that the best model for context effects on suppression by su2 involves primarily the two nucleotides 3' to the amber codon, and that their contributions are independent and additive. Context effects on 2AP mutagenesis also involve the two nucleotides 3' to the 2AP insertion, but their effects are not independent. In a construct for producing beta-galactosidase, the effects on translational yields of the tri-nucleotide 5' to the initiation codon are dependent on the entire triplet. Models based on these quantitative results are presented for each of the examples.